Valuing Ireland's Rural and Urban Inland Waterways : Recognising the Diverse Benefits and Services of the Inland Waterways and Their Role in Regional Development.: Recognising the Diverse Benefits and Services of the Inland Waterways and Their Role in Regional Development. (2016) - Waterways Ireland,; Louise Brown Research (Firm),
No abstract available